Full-Order and Simplified Dynamic Phasor Models of a Single-Phase Two-Stage Grid-Connected PV System - Udoka C. Nwaneto; Andrew M. Knight (IEEE Access, 2023)
This paper presents a study on the use of the dynamic phasor (DP) method to develop efficient simulation models for a single-phase two-stage grid-connected photovoltaic (PV) system. Two DP models, DP-Full and DP-Simp, are proposed, with the former modeling the PV array, PV capacitor, boost converter, DC-link, and MPPT (maximum power point tracking) control in detail, while the latter simplifies the DC-side model of the inverter by aggregating the PV capacitor- and boost inductor dynamics into a first-order function and calculating the MPP (maximum power point) voltage and current analytically. The accuracy and execution speed of the two DP models are verified by comparing their performance with those of a detailed switching model simulated in a commercially available electromagnetic transient program. Simulation and error calculation results show that there is a good agreement between results from the proposed DP models and the detailed switching model. The proposed DP models also demonstrate computational advantage over the detailed switching model in a multi-converter scenario, making them useful for fast-paced transient analysis of distribution grids with high PV penetrations.